A model for the effective management of information and communications technology development in schools derived from six contrasting case studies - Kirkman, Colin (Journal of information technology for teacher education, 2000)
Currently in the United Kingdom there are several major initiatives to encourage the development of information and communications technology (ICT) in schools. However, in the past many significant educational innovations have resulted in disappointing outcomes and limited curriculum change. This article presents a three-phase model that offers guidance on how to facilitate effective curriculum change, particularly in the field of ICT. The model was derived from analysing six contrasting case studies of departmental ICT within a particular secondary school (ages 12-16 years). The article discusses the main issues identified within the case studies that led to the formulation of the model. 'Issue trees' were devised as a system for hierarchically grouping and presenting the factors that encouraged and discouraged ICT development across the various departments. Important aspects of the model include: gaining a firm innovative decision from a department, selling the pedagogic benefits of the innovation, the willingness of staff to undergo professional development (particularly pedagogic development), clear and positive communication channels that facilitate responsive management, and a methodical development cycle. The model has proved a useful tool for securing the effective integration of ICT into the curriculum, i.e. teachers effectively deliver appropriate ICT activities which have been adopted by the whole department and integrated into subject work schemes.